Peningkatan Profesionalisme Guru melalui Program Pengembangan Karir Guru di MTs Bahrul Ulum Tambakberas Jombang - Putri Mey Firnanda; M. Aliyul Wafa; M. Farid Nasrulloh (MASALIQ, 2025)
The limited number of studies on teacher career development serves as the background of this research, despite its significant impact on improving the quality of education. This study aims to: (1) analyze the implementation process of teacher career development at MTs Bahrul Ulum; (2) examine the role of the school principal in managing teacher career development programs; and (3) evaluate teacher professionalism in teaching and learning activities. A descriptive qualitative approach was employed with four purposively selected research subjects directly involved in madrasah management. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings show that teacher professionalism is enhanced through participation in career development programs, both online, such as training with the Si Pintar application provided by the Ministry of Religious Affairs, and offline through KKG, MGMP, P3K, and PKMS, as well as through career advancement pathways. These results affirm the relevance of career theory, human resource development, and educational leadership. The main conclusion emphasizes the importance of the principal’s role as manager, supervisor, and educator in maintaining and improving teacher quality through regular performance evaluations. The implications include theoretical contributions to the study of teacher and educational staff management, as well as practical recommendations for policymakers to design more systematic and sustainable teacher career development strategies. This study also opens opportunities for further exploration of the dynamics of teacher professionalism within the evolving context of education.